Fabrication of drug/polymer composite particles for pharmaceutical application - Poh, Kin Hwee. (2012)
Evaporative Precipitation of Nanosuspension (EPN) was used to fabricate nanoparticles of Silymarin, a drug with low bioavailability in the human body, with the aim of enhancing its bioavailability by increasing its dissolution rate. Investigations on how varying solvent to anti-solvent ratio and drug concentration in solvent would affect the morphology as well as the dissolution properties of Silymarin particles were carried out. Also, Silymarin complexes were also fabricated by adding polymers to Silymarin using the solvent evaporation method to study the effect of polymers on the morphology as well as the dissolution properties of Silymarin particles. Characterization was done using Scanning Electron Microscopy (SEM), Differential Scanning Calorimetry (DSC) and dissolution tester to determine the properties of the fabricated particles.